2011
DOI: 10.1080/11250000903373797
|View full text |Cite
|
Sign up to set email alerts
|

Protozoa in wastewater treatment processes: A minireview

Abstract: Biological wastewater treatment is a process of increasing importance in a world with an ever-increasing human population. Wastewater treatment facilities are designed to maintain the high density and activity levels of those microorganisms that carry out the various purification processes. Protozoa are one of the most common components in these man-made ecosystems and play an important role in wastewater purification processes. Protozoa are responsible for improving the quality of the effluent, maintaining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
121
1
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(143 citation statements)
references
References 53 publications
10
121
1
11
Order By: Relevance
“…S3), which may have led to the release of flocculated non-filamentous bacteria to the liquor phase, as exemplified by increased levels of suspended solids in the effluents (SS e ) (Pearson's r between SVI and SS e : r System A = 0.520, r System B = 0.693; p < 0.05; based on the 48-h average data). It is known that the four peritrich species (actually most species of bactivorous protozoa, except for crawling ciliates) can only feed on dispersed non-filamentous bacteria and particles in BWTSs (Fenchel 1987;Madoni 2011). We thus concluded that sludge de-flocculation due to the excessive growth of filamentous bacteria (e.g.…”
Section: Microfauna Species Associated With Sludge Bulkingmentioning
confidence: 81%
See 1 more Smart Citation
“…S3), which may have led to the release of flocculated non-filamentous bacteria to the liquor phase, as exemplified by increased levels of suspended solids in the effluents (SS e ) (Pearson's r between SVI and SS e : r System A = 0.520, r System B = 0.693; p < 0.05; based on the 48-h average data). It is known that the four peritrich species (actually most species of bactivorous protozoa, except for crawling ciliates) can only feed on dispersed non-filamentous bacteria and particles in BWTSs (Fenchel 1987;Madoni 2011). We thus concluded that sludge de-flocculation due to the excessive growth of filamentous bacteria (e.g.…”
Section: Microfauna Species Associated With Sludge Bulkingmentioning
confidence: 81%
“…However, as shown in Fig. 3 and Table S3, E. plicatilis, V. striata, C. polypinum and V. cupifera, the four peritrich ciliates feeding on small dispersed bacteria (Fenchel 1987;Madoni 2011), were all inversely related to water temperature in the range from 14.5 • C to 26.3 • C (based on the 48-h average data) in both systems. That is to say, the abundances of the four species, especially E. plicatilis and V. striata, increased with the decrease in water temperature, suggesting that sludge bulking may have created some favorable conditions for the growth of these species, even under a temperature condition unfavorable for their growth.…”
Section: Microfauna Species Associated With Sludge Bulkingmentioning
confidence: 99%
“…No group or species is ever dominant over the others, even if the ratios between various groups or species differ. In contrast, microfauna that is dominated by one group indicates a trophic imbalance caused by limiting factors that impede the development of other species [27]. In this study, flowback water was added to treated wastewater for only 9 weeks.…”
Section: Microfauna Communitymentioning
confidence: 99%
“…Aspidisca is a colorless genus from fresh waters. It is quite widespread, being found on plants and in detritus of fresh waters and is an indicator of nitrate in the process of treating waste water (Renneberg et al, 2016 (Madoni, 2011). Sphaerotilus are aquatic periphitonic microorganisms associated with polluted water, sewage and activated sludge (Chapman, 1996).…”
Section: Fig 4 Amoebas Growth Curve During 2015-2016mentioning
confidence: 99%